2018
DOI: 10.1186/s12864-018-4728-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatopancreatic Necrosis Disease (AHPND) related microRNAs in Litopenaeus vannamei infected with AHPND-causing strain of Vibrio parahemolyticus

Abstract: BackgroundAcute hepatopancreatic necrosis disease (AHPND) has emerged as a major debilitating disease that causes massive shrimp death resulting in substantial economic losses in shrimp aquaculture. Given that several diseases and infections have been associated with microRNAs (miRNAs), we conducted a comparative transcriptomic analysis using the AHPND (VA) and non-AHPND (VN) strains of Vibrio parahemolyticus to identify miRNAs potentially involved in AHPND pathogenesis in Litopenaeus vannamei.ResultsA total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Small RNA libraries prepared from the NLHS-treated and VP AHPND -infected L. vannamei hemocytes (NLHS-VP) generated 3 million reads across 3 libraries, which revealed 41 DEM homologs, and 27 up-regulated and 14 down-regulated miRNAs. Previously, there were 47 up-regulated and 36 down-regulated miRNA homologs identified in VP AHPND challenged L. vannamei hemocytes 10 . In this study, eight miRNA homologs that included lva-miR-184, lva-let-7, lva-miR-9, lva-miR-305, lva-miR-71, lva-miR-2, lva-miR-274, and lva-miR-317 were found to be DEMs, similar to a previous study from 2018 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small RNA libraries prepared from the NLHS-treated and VP AHPND -infected L. vannamei hemocytes (NLHS-VP) generated 3 million reads across 3 libraries, which revealed 41 DEM homologs, and 27 up-regulated and 14 down-regulated miRNAs. Previously, there were 47 up-regulated and 36 down-regulated miRNA homologs identified in VP AHPND challenged L. vannamei hemocytes 10 . In this study, eight miRNA homologs that included lva-miR-184, lva-let-7, lva-miR-9, lva-miR-305, lva-miR-71, lva-miR-2, lva-miR-274, and lva-miR-317 were found to be DEMs, similar to a previous study from 2018 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous small RNA-Seq study has identified differentially expressed miRNAs from L. vannamei hemocytes upon VP AHPND infection. 222 shrimp miRNA target genes (involved in various biological functions) that encode proteinase inhibitors, apoptosis-related proteins, and heat shock proteins were predicted 10 . Analysis of the expression of different miRNAs, in response to bacterial infections, indicates miRNAs are contributors in the host innate immune response, and thus help to illustrate the general role of miRNAs in immunity 11 .…”
mentioning
confidence: 99%
“…Fifteen miRNAs were differentially expressed in response to heat‐stress; target gene prediction and functional annotation indicated that several shrimp cellular processes, such as signal transduction, transcription, lipid metabolism, etcetera, were subject to miRNA‐mediated regulation in response to heat‐stress (Zheng et al . ).…”
Section: Biological Functions Of Shrimp Micrornasmentioning
confidence: 99%
“…The bacteria Vibrio parahemolyticus has been associated to AHPND (Lee et al 2015), but studies from diverse perspectives are needed to understand the related pathogenic mechanisms. A recent work identified differentially expressed miRNAs following infection of shrimp with AHPND and non-AHPND strains of V. parahemolyticus (Zheng et al 2018b). The miRNA transcriptome comparative analysis, from L. vannamei, showed 47 up-regulated and 36 down-regulated miRNAs after challenge shrimp with V. parahemolyticus strains.…”
Section: Microrna Biogenesis In Penaeid Shrimpmentioning
confidence: 99%
See 1 more Smart Citation